A review on status of drug disposal practice of unused and expired drugs among different countries - Aakriti Aryal, Paulvarnan Anitha Anuba, Gopalan Ramalingam Arun, Sundararajan Sarumathy, Ramachandran Nanda kumar (Journal of Applied Pharmaceutical Science, 2023)
Medicines are crucial in treating various diseases, but when they are not needed, it is essential to dispose of them correctly. This review aims to study the status of the disposal of unused and expired drugs in different countries. The study objectives included reviewing procedures adopted by the general public for disposing of pharmaceuticals and public awareness about the problem of incorrect disposal methods. The literature search was done from PubMed and Elsevier databases, by entering the keywords “unused medications,” “expired drugs,” and “drug disposal.” Articles were excluded if they did not focus specifically on drug disposal practices. In many nations, disposing of unwanted drugs has become a burden since pharmaceutical waste permeates the ecosystem, posing a severe risk to human and environmental health. As a need of the hour, public education on proper medication disposal is required. Furthermore, the government should promote the reverse distribution practice. Residents are urged to return undesired prescriptions to pharmacies, which are collected and destroyed by approved agents or bodies.